Arbitrary Shaped Objects Detection and Reconstruction through Overset Grid Generation Method with B2-spline Interpolation in Forward-Backward Time-Stepping Inverse Scattering - Kismet, Hong-Ping; Shafrida, Binti Sahrani; Wee, Boon Siong; Moriyama, Toshifumi (The Applied Computational Electromagnetics Society, 2020)
Finite-Difference Time-Domain (FDTD) method is a simple and powerful tool used to solve electromagnetic (EM) problems. However, the drawbacks of FDTD method are difficult to model the curved boundaries and small features due to its restriction to inherent orthogonal grids. We have previously proposed that the B2-spline or biquadratic spline interpolation technique for Overset Grid Generation and FiniteDifference Time-Domain (OGG-FDTD) method be utilised to overcome the limitations of FDTD method. This proposed method has the ability to accurately measure a scattered field around an unknown object. In this paper, the OGG-FDTD method with B2-spline interpolation in Forward-Backward Time-Stepping (FBTS) inverse scattering technique was proposed for the detection and reconstruction of arbitrary shaped objects in Case A and malignant breast tumour detection in Case B. The results showed that the Mean Square Error (MSE) of reconstructed dielectric profiles by using the proposed method has achieved significantly lower values than the FDTD method in FBTS. In Case A, the accuracy difference between the two methods was 26.67% for relative permittivity and 27.63% for conductivity, respectively. In Case B, it was found that the implementation of the proposed method increased the accuracy of reconstructed the relative permittivity image by 50.54%, and conductivity by 74.42% as compared to the FDTD method in FBTS technique. Furthermore, the values of normalised error function for the proposed method were also lower than the FDTD method in FBTS. Hence, it is proven that this numerical method can provide clearer and better reconstructed images to improve the quality of retrieve the dielectric profiles of the investigation area.